Carbon-silicon skeleton oxidized metal-based catalyst and preparation method thereof

The preparation of carbon-silicon skeleton oxidation metal-based catalysts through coal gangue, and the supercritical water immersion method and plasma technology were used to solve the problems of low traditional biological treatment efficiency and high cost of coal gangue waste treatment, achieving efficient degradation of difficult-to-degrade organic wastewater and Improvement of catalyst activity.

CN119186583AActive Publication Date: 2024-12-27SHANGHAI MARITIME UNIVERSITY

Patent Information

Application Number
CN202410814573.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2024-12-27
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

Traditional biological treatment methods are not efficient in treating high concentration and difficult to degrade organic wastewater, cannot meet increasingly stringent environmental protection requirements, and there is a high cost of treating coal gangue waste.

Method used

Coal gangue is used as the preparation method of carbon-silicon skeleton oxidation metal-based catalyst, and the catalyst is prepared by supercritical water immersion method and plasma technology. The synergistic action of metal oxides such as manganese, copper, and cerium is used to improve the oxidation performance and activity of the catalyst.

Benefits of technology

Effectively degrade difficult-to-degrade organic wastewater, improve the oxidation capacity and activity of the catalyst, reduce the cost of coal gangue waste treatment, and achieve efficient degradation of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186583A_ABST
    Figure CN119186583A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-silicon skeleton oxidized metal-based catalyst and a preparation method thereof.The catalyst is prepared by using coal gangue as a carbon source and a silicon source and a carbon-silicon skeleton as a carrier through a supercritical water impregnation method, and the preparation method comprises the steps of coal gangue pretreatment, metal impurities and soluble substances are removed; the pretreated coal gangue is put into a tubular furnace, nitrogen is introduced, a reaction is carried out at the temperature of 1150-1200 DEG C, natural cooling is carried out after the reaction is completed, an obtained product is cleaned and dried, and the carbon-silicon framework is obtained; according to the present invention, the carbon-silicon skeleton is adopted as the carrier, the supercritical water impregnation method is adopted to prepare the catalyst, and the prepared catalyst is activated through the plasma technology, such that the obtained carbon-silicon skeleton oxidation metal-based catalyst has high activity and high oxidation capacity; the problem of catalytic treatment of degradation-resistant and high-difficulty organic wastewater is also effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a carbon-silicon skeleton oxidation metal-based catalyst and a preparation method thereof. Background Art

[0002] In the process of industrial development, the treatment of high-difficulty organic wastewater has always been an important issue in environmental protection and sustainable development. High-difficulty organic wastewater mainly comes from petrochemical, pharmaceutical, printing and dyeing, papermaking and other industries. These wastewaters contain a large amount of difficult-to-degrade organic substances, such as dyes, surfactants, organic solvents and various synthetic compounds. These organic substances not only have poor biodegradability, but also have high chemical oxygen demand (COD) and biological oxygen demand (BOD), which pose a serious threat to the self-purification capacity of water bodies, and direct discharge will cause great damage to the environment.

[0003] Traditional biological treatment methods are often inefficient in treating such high-concentration and difficult-to-degrade organic wastewaters and cannot meet increasingly stringent environmental protection requirements. Therefore, the development of efficient, economical and sustainable new wastewater treatment technologies has become a research hotspot. In this context, catalytic oxidation technology has become a highly promising alternative technology due to its efficient organic matter degradation ability and low operating cost. The application of catalysts in the treatment of difficult organic wastewater mainly utilizes the characteristics of catalysts to accelerate the oxidation reaction of organic pollutants, thereby achieving the purpose of purifying water quality. Carbon silicon skeleton materials are often used as catalyst carriers due to their unique physical and chemical properties, such as high specific surface area, controllable pore structure, good thermal stability and chemical stability, and excellent mechanical strength. Manganese oxides have rich oxidation states, high catalytic activity, good structural stability, easy preparation and low cost, and are suitable for a variety of catalytic reactions. They are often used as active ingredients of catalysts.

[0004] Coal gangue is a carbon-containing rock discharged from coal mines during the production process of development and excavation, coal mining and coal washing, and is an industrial solid waste in the coal mining industry. It mainly contains carbon, silicates and other components, and is a good raw material for preparing carbon-silicon skeletons. It not only reduces the cost of treating coal gangue waste, but the catalyst prepared with it as raw material can also be used to catalyze the treatment of difficult-to-degrade organic wastewater. Summary of the invention

[0005] The purpose of the present invention is to prepare a catalyst using coal gangue waste material so that the catalyst has the function of effectively treating organic wastewater.

[0006] To achieve the above objectives, the present invention proposes a carbon-silicon skeleton oxidation metal-based catalyst, which uses coal gangue as a carbon source and a silicon source, a carbon-silicon skeleton as a carrier, and is prepared by a supercritical water impregnation method, and has the catalytic ability to catalyze the treatment of difficult-to-degrade organic wastewater.

[0007] The present invention also provides a method for preparing a carbon-silicon skeleton oxidized metal-based catalyst, and the preparation of the carbon-silicon skeleton oxidized metal-based catalyst comprises the following steps:

[0008] 1) Pretreatment of coal gangue: crushing the coal gangue into fine particles and removing metal impurities and soluble substances;

[0009] 2) Preparation of carbon-silicon skeleton: placing the pretreated coal gangue into a tubular furnace, introducing nitrogen, reacting at a temperature of 1150-1200° C., cooling naturally after the reaction is completed, washing and drying the obtained product, and obtaining a carbon-silicon skeleton;

[0010] 3) Using the carbon silicon skeleton as a carrier, the catalyst is prepared by supercritical water impregnation method, and the prepared catalyst is activated by plasma technology, and then cleaned and dried to obtain a carbon silicon skeleton oxidation metal-based catalyst.

[0011] Further, in step 1), the pre-processing is specifically:

[0012] 1.1: crush the coal gangue into fine particles with a particle size of less than 5 mm, and remove large particles of hard impurities;

[0013] 1.2: Take 20-25g of crushed coal gangue and place it in a 500ml beaker. Add 37% hydrochloric acid to the beaker and stir it gently with a glass rod to dissolve some impurities in the coal gangue, including iron oxide, aluminum oxide or calcium oxide.

[0014] 1.3: Place the treated gangue in a muffle furnace for calcination to help decompose the organic matter in the gangue and release carbon. The calcination temperature is 1100-1200℃, the heating rate is 6-8℃ / min, and the calcination time is 3-4h. After calcination, cool it down to room temperature naturally and take out the gangue;

[0015] 1.4: After the gangue is washed with deionized water for 3-5 times until the pH of the solution is close to neutral, the gangue is filtered and dried in an oven at 40-45°C. The drying process takes 10-12 hours. The gangue is then taken out to obtain pretreated gangue, at which point the main components of the gangue are carbon and silicate.

[0016] Further, in step 2), the specific method for preparing the carbon silicon skeleton is: take 10-15g of pretreated coal gangue, crush it into powder, mix it with an activator (1-1.2g of K2CO3, 1-1.4g of NaOH, 1.5-2g of Znc l2), 20-25ml of kapok pulp powder and deionized water, and knead it into a ball, then place the ball into a quartz boat of a tubular furnace, place the quartz boat of the tubular furnace in the center of the tubular furnace to ensure uniform temperature distribution, set the tubular furnace temperature to 1150-1200℃, and heat it at a rate of 10-12℃ / min. In addition, introduce nitrogen as a protective atmosphere, keep warm at the set temperature for 8-10h, and then cool it naturally to room temperature. After the tubular furnace is cooled, take out the resulting product, and rinse the product 3-5 times with 2-5% dilute hydrochloric acid and deionized water to obtain the carbon silicon skeleton. The activator can help form more pores, and the kapok pulp can introduce a pore structure into the silicon-carbon skeleton on the one hand, and can serve as a supplementary carbon source on the other hand.

[0017] Further, in step 3), the catalyst is prepared by supercritical water impregnation. The diffusion coefficient and mass transfer performance of supercritical water are between those of gas and liquid, which enables the dissolved substances to be distributed more quickly and evenly on the carrier material. Therefore, the catalyst is prepared by this method, and no harmful organic solvents are required in the preparation process, which can increase the reaction rate. Due to the high penetration and mass transfer capacity of supercritical water, the catalyst precursor can be more evenly dispersed on the carrier. This helps to improve the availability and catalytic efficiency of the active sites of the catalyst. The specific steps are:

[0018] 3.1: Take 2-2.5g of carbon silicon skeleton and 10ml of 18-20% Mn(NO3)2 in a reactor, add 10ml of deionized water, set the temperature to 573-583k, preheat at this temperature, apply pressure of 221-250bar, and immerse under steady-state conditions for 1-1.2 hours;

[0019] 3.2: Then, the pressure of the reactor is slowly reduced and cooled to room temperature, the solid semi-finished catalyst is separated, and washed with anhydrous ethanol to remove unreacted impurities, etc.;

[0020] 3.3: Place the cleaned semi-finished catalyst in an oven and dry it at 35-40°C;

[0021] 3.4: Mix 4-5g of the semi-finished catalyst with 5-6g of anhydrous copper sulfate, 6-7g of cerium nitrate hexahydrate and 300-350ml of deionized water, stir continuously with a glass, and then add 30ml of 10% sodium hydroxide solution to obtain a mixed solution. Centrifuge the mixed solution for 3-5 times, then place the obtained powder in a muffle furnace, heat it to 700-750℃ at a rate of 8-10℃ / min, keep it warm at this temperature for 3-3.5h, wait for the muffle furnace to cool to room temperature, and take out the catalyst. At this time, the catalyst contains three metal oxides: cerium oxide, copper oxide and manganese dioxide. Compared with one metal oxide, the three of them have a good synergistic effect, which can increase the oxidation performance of the catalyst, produce more hydroxyl radicals, and more effectively treat pollutants. On the other hand, cerium oxide and copper oxide can not only effectively remove heavy metal particles in wastewater, but also reduce the bacterial content of wastewater. It has a certain bactericidal effect;

[0022] 3.5: Take out 10-15g of the prepared catalyst and put it into a plasma reactor, use argon as the discharge atmosphere, the gas flow rate is 100-120ml / min, the input power is 10-20w, the discharge time is 10-15min, and perform plasma activation. Through plasma activation, a new surface structure and active sites can be formed on the surface of the catalyst, and part of the impurities on the surface of the catalyst can be removed to expose more active sites. Improve the catalytic activity of the catalyst. After the activation reaction is completed, wash the catalyst with deionized water 3-5 times, put it in an oven at 40-45℃ and dry it for 5-6h, then take it out to obtain a carbon silicon skeleton oxidation metal-based catalyst.

[0023] Furthermore, in step 3.4, the mixed solution is centrifuged for 3-5 times, specifically: after the mixed solution is placed in a centrifuge, it is rapidly centrifuged at a speed of 5000-6000 r / min, and then washed with deionized water, and this step is repeated 3-5 times.

[0024] Furthermore, when the catalyst, hydrogen peroxide and sodium hypochlorite are present at the same time, the optimal effect of organic degradation is achieved. The concentration ranges of the catalyst, hydrogen peroxide and sodium hypochlorite are respectively 85-95 g / L for the catalyst, 4.5-5.5 ml / L for hydrogen peroxide and 2.2-2.6 g / L for sodium hypochlorite.

[0025] Furthermore, the weight ratio of each component in the catalyst is: coal gangue: 18-20% manganese nitrate solution: anhydrous copper sulfate: cerium nitrate = 10-12: 11-12: 10-12: 12-14.

[0026] Compared with the prior art, the advantages of the present invention are:

[0027] 1. The carbon-silicon skeleton oxide metal-based catalyst prepared by the present invention uses coal gangue waste as a carbon source and a silicon source, which can effectively reduce the discharge of waste. It not only reduces the cost of treating coal gangue waste, but also the catalyst prepared with it as a raw material is effectively used for catalytic treatment of difficult-to-degrade organic wastewater, and has excellent catalytic ability.

[0028] 2. The carbon silicon skeleton oxidation metal-based catalyst prepared by the present invention is prepared by supercritical water impregnation in the preparation room, which effectively improves the oxidation ability of the catalyst, and is activated by plasma technology, thereby further improving the activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope schematic diagram of a carbon-silicon skeleton oxidation metal-based catalyst according to an embodiment of the present invention;

[0030] Figure 2 This is a diagram showing the status of the osmotic agent wastewater in the experimental group 1 at different times during the process of the second experiment in the embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further described below.

[0032] This embodiment provides a carbon silicon skeleton oxidation metal-based catalyst, and the preparation method thereof is as follows:

[0033] Step 1: Gangue pretreatment

[0034] (1.1) Grind the coal gangue into fine particles with a particle size of less than 5 mm and remove the large particles and hard impurities.

[0035] (1.2) Take 20-25g of crushed coal gangue and place it in a 500ml beaker. Add 37% hydrochloric acid to the beaker and stir gently with a glass rod to dissolve some impurities in the coal gangue, such as iron oxide, aluminum oxide or calcium oxide.

[0036] (1.3) The treated gangue is placed in a muffle furnace for calcination to help decompose the organic matter in the gangue and release carbon. The calcination temperature is 1100-1200℃, the heating rate is 6-8℃ / min, and the calcination time is 3-4h. After calcination, it is naturally cooled to room temperature and the gangue is taken out.

[0037] (1.4) After the coal gangue is washed with deionized water for 3-5 times until the pH of the solution is close to neutral, the coal gangue is filtered and placed in an oven at 40-45°C for drying. The drying process takes 10-12 hours, and then the coal gangue is taken out to obtain pretreated coal gangue. At this time, the main components of the coal gangue are carbon and silicate.

[0038] Step 2: Preparation of carbon silicon skeleton

[0039] (2.1) Take 10-12g of pretreated coal gangue, crush it into powder, mix it with activator (1-1.2g of K2CO3, 1-1.4g of NaOH, 1.5-2g of ZnCl2), 20-25ml of kapok pulp powder and deionized water, and knead it into a ball.

[0040] (2.2) Place the mass into a quartz boat of a tube furnace, place the quartz boat in the center of the tube furnace to ensure uniform temperature distribution, set the temperature of the tube furnace to 1150-1200°C, and increase the temperature at a rate of 10-12°C / min. In addition, introduce nitrogen as a protective atmosphere, keep the temperature at the set temperature for 8-10 hours, and then cool naturally to room temperature. After the tube furnace is cooled, take out the product.

[0041] (2.3) The product is washed 3-5 times with 2-5% dilute hydrochloric acid and deionized water to obtain a carbon silicon skeleton.

[0042] Step 3: Preparation of carbon-silicon framework oxidation metal-based catalyst

[0043] (3.1) Take 2-2.5g of carbon silicon skeleton and 10ml of 18-20% Mn(NO3)2 in a reactor, add 10ml of deionized water, set the temperature to 573-583K, preheat at this temperature, apply pressure of 221-250bar, and immerse under steady-state conditions for 1-1.2 hours.

[0044] (3.2) The reactor pressure is then slowly reduced and cooled to room temperature, the solid semi-finished catalyst is separated and washed with anhydrous ethanol to remove unreacted impurities.

[0045] (3.3) Place the cleaned semi-finished catalyst in an oven and dry it at 35-40°C.

[0046] (3.4) Mix 5-6g of the semi-finished catalyst with 5-6g of anhydrous copper sulfate, 6-7g of cerium nitrate hexahydrate and 300-350ml of deionized water, stir continuously with a glass cup, and then add 30ml of 10% sodium hydroxide solution to obtain a mixed solution. Place the mixed solution in a centrifuge and perform rapid centrifugation at a speed of 5000-6000r / min. Then, wash with deionized water, and repeat this step 3-5 times. Then, place the obtained powder in a muffle furnace, heat it to 700-750℃ at a rate of 8-10℃ / min, keep it at this temperature for 3-3.5h, wait for the muffle furnace to cool to room temperature, and take out the catalyst.

[0047] (3.5) Take out 10-15g of the prepared catalyst and put it into a plasma reactor, use argon as the discharge atmosphere, the gas flow rate is 100-120ml / min, the input power is 10-20w, the discharge time is 10-15min, and carry out plasma activation. After completion, wash the catalyst with deionized water 3-5 times, put it into an oven at 40-45℃ and dry it for 5-6h, then take it out to obtain a carbon silicon skeleton oxide metal-based catalyst.

[0048] The obtained carbon silicon skeleton oxidation metal-based catalyst was subjected to electron microscope scanning, such as Figure 1 As shown in the figure, it can be seen that the catalyst presents a coral reef-like morphology under a 50,000-fold magnification environment, with many micron-sized holes inside. The specific surface area of ​​the catalyst in this example is 271 m 2 / g, the test results are Figure 1 The results are consistent with those of the scanning electron microscopy images shown.

[0049] Experiment 1

[0050] The carbon silicon skeleton oxidation metal-based catalyst prepared in the implementation was used to treat the model pollutants methylene blue and phenol as well as the penetrant flaw detection wastewater of a certain factory, wherein the catalyst addition amount was 71g / L, the hydrogen peroxide addition amount was 5.5ml / L, and the sodium hypochlorite addition amount was 2.5g / L. Hydrogen peroxide can combine with the active sites on the catalyst surface to effectively treat the pollutants, and sodium hypochlorite can break the long chain of the pollutant to form a short chain, which is conducive to further degradation, and on the other hand, it can effectively combine with hydrogen peroxide to produce singlet oxygen free radicals to further degrade the pollutants. The treatment results are shown in Table 1 below:

[0051] Table 1 Simulation results of Experiment 1

[0052]

[0053] As can be seen from Table 1, the catalyst prepared in the embodiment of the present invention can achieve degradation rates of 88% and 92% for the model pollutants methylene blue and phenol, which can effectively degrade the model pollutants. The degradation rate for the penetrant wastewater discharged from the factory can also reach 90%, which has great application value in actual production.

[0054] Experiment 2

[0055] The carbon silicon skeleton oxidation metal-based catalyst, NaCl solution and H2O2 solution of this embodiment were mixed in different concentrations to treat penetrant inspection wastewater. The penetrant wastewater was treated according to the four groups of different concentration components shown in Table 2. After 4 hours of treatment, the experimental group 1, the experimental group 2, the experimental group 3 and the experimental group 4 were sampled respectively to measure COD and chromaticity. The results are shown in Table 2, wherein the ultraviolet spectrophotometer was used to measure the chromaticity in this experiment 2:

[0056] Table 2 Simulated treatment scheme and results of penetrant testing wastewater in Experiment 2

[0057]

[0058] As can be seen from Table 2, the addition amount of catalyst, oxide hydrogen peroxide and hypochlorous acid has a greater impact on the degradation rate of COD. When any one of the catalyst, hydrogen peroxide and sodium hypochlorite is less, the COD degradation rate will be reduced. The COD removal rate of the third experimental group is the lowest. This is because there is no hydrogen peroxide, which makes it difficult to produce hydroxyl radicals to degrade organic pollutants. The addition amount of sodium hypochlorite mainly affects the removal of chromaticity, mainly because sodium hypochlorite can break the long chain of organic matter, thereby reducing the chromaticity of organic matter. Therefore, in general, only when the catalyst, hydrogen peroxide and sodium hypochlorite of the present invention are present at the same time, can the efficient degradation treatment of organic matter be achieved.

[0059] In the treatment process of the above experiment 2, samples were taken to observe the status of the penetrant testing wastewater in the experimental group 1 after 1h, 2h, 3h, and 4h of treatment. Figure 2 As shown, the four test tubes from left to right are pictures of the wastewater after 1h, 2h, 3h and 4h of reaction. It can be seen that after 4 hours, the color of the wastewater is basically degraded from the original red to colorless, further proving the efficient degradation ability of the catalyst in this example on organic matter.

[0060] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.

Claims

1. A carbon-silicon skeleton oxidation metal-based catalyst, characterized in that: The catalyst uses coal gangue as a carbon source and a silicon source, takes a carbon-silicon skeleton as a carrier, is prepared by a supercritical water impregnation method, and has the catalytic ability to catalyze and treat difficult-to-degrade organic wastewater.

2. A method for preparing a carbon-silicon skeleton oxidized metal-based catalyst, comprising preparing the carbon-silicon skeleton oxidized metal-based catalyst as claimed in claim 1, characterized in that: The steps include: 1) Pretreatment of coal gangue: crushing the coal gangue into fine particles and removing metal impurities and soluble substances; 2) Preparation of carbon-silicon skeleton: placing the pretreated coal gangue into a tubular furnace, introducing nitrogen, reacting at a temperature of 1150-1200° C., cooling naturally after the reaction is completed, washing and drying the obtained product, and obtaining a carbon-silicon skeleton; 3) Using the carbon silicon skeleton as a carrier, the catalyst is prepared by supercritical water impregnation method, and the prepared catalyst is activated by plasma technology, and then cleaned and dried to obtain a carbon silicon skeleton oxidation metal-based catalyst.

3. The method for preparing the carbon-silicon skeleton oxidized metal-based catalyst according to claim 2, characterized in that: In step 1), the pretreatment is specifically: 1.1: crushing the coal gangue to a particle size less than 5 mm; 1.2: Place the crushed coal gangue in a beaker, add 37% hydrochloric acid into the beaker, and stir gently to dissolve some impurities; 1.3: Place the treated coal gangue in a muffle furnace for calcination at a temperature of 1100-1200°C, a heating rate of 6-8°C / min, and a calcination time of 3-4h. After calcination, cool naturally to room temperature and take out the coal gangue; 1.4: The coal gangue is washed with deionized water for 3-5 times, filtered, and dried in an oven at 40-45° C. to obtain pretreated coal gangue.

4. The method for preparing the carbon-silicon skeleton oxidized metal-based catalyst according to claim 3, characterized in that: In step 2), the specific method for preparing the carbon silicon skeleton is: take the pretreated coal gangue, crush it into powder, mix it with the activator, kapok pulp powder and deionized water, and knead it into a ball, then place it in a quartz boat of a tube furnace, set the tube furnace temperature to 1150-1200°C, and heat it at a rate of 10-12°C / min. In addition, nitrogen is introduced as a protective atmosphere, and the mixture is kept warm at the set temperature for 8-10 hours, then naturally cooled to room temperature. After cooling, the product is taken out and rinsed with dilute hydrochloric acid and deionized water for 3-5 times to obtain the carbon silicon skeleton.

5. The method for preparing the carbon-silicon skeleton oxidized metal-based catalyst according to claim 4, characterized in that: Step 3) is specifically: 3.1: Place the carbon silicon skeleton and 18-20% Mn(NO3)2 in a reactor, add deionized water, set the temperature to 573-583K for preheating, apply a pressure of 221-250bar, and immerse for 1-1.2 hours under steady-state conditions; 3.2: Slowly reduce the pressure of the reactor and cool it to room temperature, separate the solid semi-finished catalyst, and wash it with anhydrous ethanol; 3.3: Place the cleaned semi-finished catalyst in an oven and dry it at 35-40℃; 3.4: The semi-finished catalyst is mixed with anhydrous copper sulfate, cerium nitrate hexahydrate and deionized water, and then sodium hydroxide solution is added to obtain a mixed solution. The mixed solution is centrifuged for 3-5 times, and then the obtained powder is placed in a muffle furnace, and the temperature is increased to 700-750°C at a rate of 8-10°C / min, and the temperature is kept at this temperature for 3-3.5h, and the muffle furnace is cooled to room temperature by itself, and the catalyst is taken out; 3.5: Place the prepared catalyst into a plasma reactor, use argon as the discharge atmosphere, a gas flow rate of 100-120 ml / min, an input power of 10-20 w, and a discharge time of 10-15 min for plasma activation. After completion, wash it with deionized water for 3-5 times, place it in an oven at 40-45 ° C and dry it for 5-6 hours, then take it out to obtain the final carbon silicon skeleton oxidation metal-based catalyst.

6. The method for preparing the carbon-silicon skeleton oxidized metal-based catalyst according to claim 5, characterized in that: In step 3.4, the mixed solution is centrifuged for 3-5 times, specifically, the mixed solution is placed in a centrifuge, centrifuged at a speed of 5000-6000 r / min, and then washed with deionized water, and the process is repeated 3-5 times.

7. The method for preparing the carbon-silicon skeleton oxidized metal-based catalyst according to claim 2, characterized in that: When the catalyst, hydrogen peroxide and sodium hypochlorite exist simultaneously, the optimal effect of degrading organic matter is achieved.

Citation Information

Patent Citations

  • Preparation method and application of desulfurization catalyst

    CN108479744A

  • Coal gangue-based catalytic material as well as preparation method and application thereof

    CN114272925A

  • Copper-doped iron metal-organic framework, preparation method thereof, and application method for activation of persulfate to treat organic wastewater

    US20180185828A1

Cited By

  • Preparation method and application of coal gangue-based geopolymer microspheres

    CN122605559A